Effectiveness of a virtual program for OSCE preparation during COVID-19: a descriptive and repeated cross-sectional study among nursing students - Rinat Avraham; Tanya Cohen; Rada Artzi-Medvedik; Nancy Hurvitz; Odeya Cohen (BMC, 2023)
Abstract Background Despite the prevalence of distance learning during COVID-19, conducting clinical training for nursing students remains challenging. In compliance with social-distancing restrictions, a Zoom-based virtual OSCE preparation program for nursing students was designed, and it included clinical skills. The aims of this study were to assess nursing students' satisfaction with a virtual program for Objective Structured Clinical Examination (OSCE) preparation, and to evaluate its learning outcomes measured by OSCE scores as compared to those of in-person preparation programs. Methods A descriptive and repeated cross-sectional study was designed. Students' satisfaction with the virtual program was based on a post-course survey and personal reflections. OSCE scores of graduates of the virtual program (n = 82) tested in 2021 were compared to those of 337 graduates of in-person programs tested in 2017-2020. Results A post-program survey revealed that 88% of the students in 2021 were satisfied with the virtual program and felt it prepared them properly for the OSCE (26% agree and 62% strongly agree). No significant differences were found between OSCE scores following the virtual program conducted in 2021 and scores following in-person programs conducted in 2017-2020. Conclusions This study suggests that nursing education can benefit from integrating virtual programs which incorporate clinical practices into the curricula, without harming student competency. The study results may address the problem of maintaining clinical practices in a time of limited accessibility, and in settings of low resources. It is important to expand the investigation to long-term impact of virtual training programs on nursing students' competencies.